2005
DOI: 10.1007/s00216-005-3382-2
|View full text |Cite
|
Sign up to set email alerts
|

Determination of free and total sulfur dioxide in wine samples by vapour-generation inductively coupled plasma–optical-emission spectrometry

Abstract: Sulfur dioxide (SO(2)) is used as a preservative and stabilizer in wine production to prevent undesired biochemical processes in the must and the final product. The concentration of SO(2) is restricted by national regulations. There are two main forms of SO(2) in wine-free (inorganic forms) and bound (fixed to organic compounds, e.g. aldehydes). Iodometric titration is commonly employed for determination of SO(2) concentration (either by direct titration or after pre-separation by distillation); other techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 23 publications
0
3
0
5
Order By: Relevance
“…For example, the RF strain‐fermented mulberry wine showed the highest alcohol content, followed by the wine fermented by RV wine and ES wine. Free sulfur in wine is mainly comprised inorganic compounds, including SO 2 , H 2 SO 3 , HSO3, and SO32 (Čmelík, Machát, Niedobová, Otruba, & Kanický, ). It was observed that these mulberry wine samples contained the similar content of the free sulfur.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the RF strain‐fermented mulberry wine showed the highest alcohol content, followed by the wine fermented by RV wine and ES wine. Free sulfur in wine is mainly comprised inorganic compounds, including SO 2 , H 2 SO 3 , HSO3, and SO32 (Čmelík, Machát, Niedobová, Otruba, & Kanický, ). It was observed that these mulberry wine samples contained the similar content of the free sulfur.…”
Section: Resultsmentioning
confidence: 99%
“…The supernatants from centrifuged samples were assayed for total SO 2 , by improved iodometric titration [13]. Sulfite concentrations are expressed as SO 2 .…”
Section: Sulfite and Hydrogen Sulfide Assaysmentioning
confidence: 99%
“…High concentrations of SO 2 inhibit the vinification process. 11 There are numerous methods for determining the concentration of SO 2 in wine. The two most common methods are the aeration−oxidation method and the Ripper method.…”
Section: Introductionmentioning
confidence: 99%